f(x) = 6x2 + 2x − 12


label Algebra
account_circle Unassigned
schedule 1 Day
account_balance_wallet $5

f(x) = 6x2 + 2x − 12

when 

f is square root of 2=

Feb 9th, 2015

f(sqrt(2)) = 6sqrt(2)^2 + 2sqrt(2) - 12

= 6*2 + 2 sqrt(2) - 12

= 2 sqrt (2)

Feb 9th, 2015

Did you know? You can earn $20 for every friend you invite to Studypool!
Click here to
Refer a Friend
...
Feb 9th, 2015
...
Feb 9th, 2015
Nov 24th, 2017
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle
Final Answer

Secure Information

Content will be erased after question is completed.

check_circle
Final Answer